Photon-induced tunability of the thermospin current in a Rashba ring. (15th March 2018) - Abdullah, Nzar Rauf; Arnold, Thorsten; Tang, Chi-Shung; Manolescu, Andrei; Gudmundsson, Vidar
Abstract: The goal of this work is to show how the thermospin polarization current in a quantum ring changes in the presence of Rashba spin–orbit coupling and a quantized single photon mode of a cavity the ring is placed in. Employing the reduced density operator and a general master equation formalism, we find that both the Rashba interaction and the photon field can significantly modulate the spin polarization and the thermospin polarization current. Tuning the Rashba coupling constant, degenerate energy levels are formed corresponding to the Aharonov–Casher destructive phase interference in the quantum ring system. Our analysis indicates that the maximum spin polarization can be observed at the points of degenerate energy levels due to spin accumulation in the system without the photon field. The thermospin current is thus suppressed. In the presence of the cavity, the photon field leads to an additional kinetic momentum of the electron. As a result the spin polarization can be enhanced by the photon field.